Analisis Pemanfaatan Kartu Indonesia Sehat (KIS) Oleh Mahasiswa KESOS USU Stambuk 2021 - Eflin Novita Sinaga; Ulina Tassia Hutagaol; Dito Pranata; Berlianti Berlianti (Jurnal Kajian dan Penelitian Umum, 2024)
The state guarantees citizens' healthcare services as regulated in the Constitution. The Indonesia Health Card (KIS) is a tangible form of the government’s effort to realize equitable and easily accessible healthcare quality for all Indonesians. However, the implications of this program have not been evenly distributed, as experienced by students in the social welfare department of Sumatera Utara University class of 2021. KIS is very beneficial for students who are aware of and can access it, but the program’s effectiveness is still hindered by uneven information distribution and complex administrative procedures. Recommendations are provided to enhance information dissemination and simplify administrative procedures to ensure the KIS program is more inclusive and easily accessible to all students.